(untitled) (Bangladesh Journal of Medical Science, 2019)
Background and Rationale: Incidence of erectile dysfunction is rising in both developing and developed countries including Bangladesh. Even in this 21st century people attracted to the herbal and/alternative medicine. The present study was aimed to evaluate the effect of Haab-e-Munish in the treatment using the International Index of Erectile Function-5 (IIEF-5) questionnaire. Material and Methods: A total 33 married male subjects participated in this study. The study was approved by the Research and Ethics Committee of the Ibn Sina Medical College & Hospital. Informed written consent was obtained from each participant. Data were expressed as mean±SD and were managed by SPSS for Windows Version 17. P<0.05 was considered significant. Results: Mean (SD) age of the participants was 36.8±7.7. Basic data like pulse, blood pressure, serum creatinine, urea and alanine aminotransferase (ALT) were unchanged compared to the baseline. IIEF Score of all five functional domain demonstrated significant improvement from the baseline. Conclusion: Herbal preparation Haab-e-Munish has positive effect in improving erectile dysfunctions and is safe for liver and kidney function on short term basis. Bangladesh Journal of Medical Science Vol.19(1) 2020 p.176-179